Autologous stem cell therapy in knee osteoarthritis: a systematic review of randomised controlled trials. Issue 20 (26th May 2021) - Wiggers, Tom GH; Winters, Marinus; Van den Boom, Noortje AC; Haisma, Hidde J; Moen, Maarten H
Abstract : Objective: Stem cell therapy is increasingly used for knee osteoarthritis (KOA). We aimed to review the evidence of autologous mesenchymal stem cell therapy on pain, function and severity on imaging in KOA. Design: Systematic review of randomised controlled trials (RCTs). Eligibility criteria: RCTs evaluating autologous mesenchymal stem cell (MSC) therapy on patient-reported outcome measures and disease severity. Data sources: Seven databases were searched until 31 December 2020. Risk of bias and data synthesis: Risk of bias was assessed using the ROB V.2. We used Grading of Recommendations Assessment, Development and Evaluation to appraise the certainty of the evidence. Data were synthesised descriptively. Results: Fourteen RCTs were included. A total of 408 patients with KOA received MSC therapy derived from bone marrow, adipose tissue or activated peripheral blood. After 1 year, 19 of 26 (73%) clinical outcome measures improved with MSCs compared with control. In the MSC group, patients improved by 1.8–4.4 points on the Visual Analogue Scale (0–10) and 18–32 points of the Knee Osteoarthritis Outcome Score (0–100). Four studies showed better disease severity on imaging after MSC compared with control at 1 year. Ten of 14 (71%) RCTs were at high risk of bias on all outcomes. No serious adverse events were reported after MSC therapy during a maximum of 4 years follow-up. Conclusion: We found a positive effect of autologous MSC therapy compared with control treatments on patient-reported outcome measures, and disease severity. The certainty of this evidence was low to very low. PROSPERO registration number: CRD42019120506